DISTRIBUTION AND COMPOSITION OF THE MAIN ACTIVE COMPONENTS FOUND IN STINGLESS BEE PROPOLIS FROM VARIOUS REGIONS IN INDONESIA - MAHANI; MICHELLE; CAHYANA, YANA; SULAEMAN, AHMAD; HARDINSYAH; NURJANAH, NUNUNG; SUNARNO; SARIADJI, KAMBANG (International Journal of Pharmacy and Pharmaceutical Sciences, 2021)
Objective: The aim of this study is to map out the distribution and composition of the main active components found in stingless bee propolis from various regions in Indonesia. Methods: The stingless bee propolis used was obtained from ten different provinces in Indonesia and the active components analysis using Gas Chromatography-Mass Spectrometer (GC-MS) pyrolyzer. Results: This study found 85 main types of active components with concentrations of ≥ 1%. The most frequently found active component was alpha-d-glucopyranoside, which had an average concentration of 28.20%. Conclusion: There were differences between the main active components found in 14 samples of stingless bee propolis obtained from 10 provinces in Indonesia, which was due to the variety of bee species and plant origin.